Estimation of the exchange of sulphur pollution over the Balkan region in 1995?2000. (14th February 2008) - Chervenkov, Hristo; Syrakov, Dimiter; Prodanova, Maria
The Bulgarian dispersion model 'Eulerian Model for Air Pollution' (EMAP) is used to estimate the sulphur pollution over the Balkan region for the period 1995?2000. A subdomain of the European Monitoring and Evaluation Programme (EMEP) grid is chosen containing 12 countries. The computational grid in this domain has a space step of 25 km, twice as fine as the EMEP grid. The former operational DWD 'Europa-Model' is used as meteorological driver. The source input is the official EMEP emission data. Monthly calculations are made having the last moment fields from the previous month as initial conditions for the next one. The boundary conditions are set to zero, so the influence of other European sources is not accounted for in this study. According to the EMEP methodology, multiple runs are made setting every time the sources of various countries to zero. The impact of every country in the pollution of all others is estimated.